2024
DOI: 10.1021/acsami.4c03861
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coordination Environment Engineering on PtxCu1–x Alloy Catalysts for the Efficient Photocatalytic Reduction of CO2 to CH4

Xin Wang,
Haohong Liao,
Wei Tan
et al.

Abstract: Alloy catalysts have been reported to be robust in catalyzing various heterogeneous reactions due to the synergistic effect between different metal atoms. In this work, aimed at understanding the effect of the coordination environment of surface atoms on the catalytic performance of alloy catalysts, a series of Pt x Cu 1−x alloy model catalysts supported on anatase-phase TiO 2 (Pt x Cu 1−x /Ti, x = 0.4, 0.5, 0.6, 0.8) were developed and applied in the classic photocatalytic CO 2 reduction reaction. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…17–20 For instance, Xiong et al and Wang et al respectively supported alloy nanoparticles (Pd x Cu 1 or Pt x Cu 1− x ) on TiO 2 to synthesize alloy photocatalysts innovatively. 21,22 The results showed that the alloy co-catalysts improved CO 2 activation and promoted carrier separation, which led to excellent photocatalytic CO 2 -to-CH 4 conversion performance. Introduction of alloy NPs could reduce the Schottky barrier and accelerate the charge migration at the semiconductor–alloy interface.…”
Section: Introductionmentioning
confidence: 99%
“…17–20 For instance, Xiong et al and Wang et al respectively supported alloy nanoparticles (Pd x Cu 1 or Pt x Cu 1− x ) on TiO 2 to synthesize alloy photocatalysts innovatively. 21,22 The results showed that the alloy co-catalysts improved CO 2 activation and promoted carrier separation, which led to excellent photocatalytic CO 2 -to-CH 4 conversion performance. Introduction of alloy NPs could reduce the Schottky barrier and accelerate the charge migration at the semiconductor–alloy interface.…”
Section: Introductionmentioning
confidence: 99%